Age and gender dependent development of Theory of Mind in 6- to 8-years old children - Calero, Cecilia I.; Salles, Alejo; Semelman, Mariano; Sigman, Mariano (Frontiers in Human Neuroscience, 2013)
The ability to attribute different mental states to distinct individuals, or Theory of Mind (ToM), is widely believed to be developed mostly during preschool years. How different factors such as gender, number of siblings or coarse personality traits affect this development is not entirely agreed upon. Here, we introduce a computerized version of the scaled ToM suite of tasks introduced by Wellman and Liu (2004), which allows us to meaningfully test ToM development on children 6 to 8-years old. We find that kids this age are still not entirely proficient in all ToM tasks, and continue to show a progression of performance with age. By testing this age range, too, we are able to observe a significant advantage of girls over boys in ToM performance. Other factors such as number of siblings, birth order, and coarse personality traits show no significant relation with the ToM task results. Finally, we introduce a novel way to quantify the scaling property of the suite involving a sequence of set inclusions and also, a comparison between specially tailored sets of logistic models. These measures confirm the validity of the scale in the 6 to 8-years old range.